TINJAUAN YURIDIS DISPENSASI PENGGUNAAN HELM PADA PENGENDARA DAN PENUMPANG SEPEDA MOTOR YANG BERPAKAIAN ADAT - Ave Christina Hananda; ardhya, si ngurah; Adnyani, Ni Ketut Sari; Kusuma, putu riski ananda (Universitas Pendidikan Ganesha, 2025)
This research aims to (1) analyze and examine the form of dispensation for the use of helmets for motorbike riders and passengers based on the Decree of the Governor of the Regional Head of Level I Bali Number 217 of 1986 Article 4 Paragraph (1) and Paragraph (2) with Article 106 Paragraph (8) of the Law -Law Number 22 of 2009 concerning Road Traffic and Transportation, (2) analyzes the regulations on the use of helmets in terms of traditional clothing which is more appropriate to use in the Decree of the Governor of the Head of the Level I Region of Bali Number 217 of 1986 Prodi Ilmu Hukum 1 Article 4 Paragraph (1) and Paragraph (2) With Article 106 Paragraph (8) of Law Number 22 of 2009 concerning Road Traffic and Transportation. The type of research used in this research is normative juridical research which aims to identify forms of norm conflict that occur between the two laws and regulations. Using a statutory approach and a conceptual approach. The sources of legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. The legal material collection technique used is through document study techniques. The legal material analysis technique used is a vertical synchronization analysis technique. The results of this research show (1) The form of dispensation for the use of helmets for motorbike riders and passengers based on the Decree of the Governor of the Regional Head of Level I Bali, namely when there is a head injury, use traditional clothing within a radius of 10 Km with a maximum speed of 40 Km per hour, (2) Regulations The more appropriate use of a helmet when wearing traditional clothing is Law Number 22 of 2009 concerning Road Traffic and Transportation because it is a law that is at a higher level than the Decree of the Governor of the Level I Regional Head of Bali.